Blood glucose level reconstruction as a function of transcapillary glucose transport - Koutny, Tomas (Computers in biology and medicine, 2014)
A diabetic patient occasionally undergoes a detailed monitoring of their glucose levels. Over the course of a few days, a monitoring system provides a detailed track of their interstitial fluid glucose levels measured in their subcutaneous tissue. A discrepancy in the blood and interstitial fluid glucose levels is unimportant because the blood glucose levels are not measured continuously. Approximately five blood glucose level samples are taken per day, and the interstitial fluid glucose level is usually measured every 5min. An increased frequency of blood glucose level sampling would cause discomfort for the patient; thus, there is a need for methods to estimate blood glucose levels from the glucose levels measured in subcutaneous tissue. The Steil-Rebrin model is widely used to describe the relationship between blood and interstitial fluid glucose dynamics. However, we measured glucose level patterns for which the Steil-Rebrin model does not hold. Therefore, we based our research on a different model that relates present blood and interstitial fluid glucose levels to future interstitial fluid glucose levels. Using this model, we derived an improved model for calculating blood glucose levels. In the experiments conducted, this model outperformed the Steil-Rebrin model while introducing no additional requirements for glucose sample collection. In subcutaneous tissue, 26.71% of the calculated blood glucose levels had absolute values of relative differences from smoothed measured blood glucose levels less than or equal to 5% using the Steil-Rebrin model. However, the same difference interval was encountered in 63.01% of the calculated blood glucose levels using the proposed model. In addition, 79.45% of the levels calculated with the Steil-Rebrin model compared with 95.21% of the levels calculated with the proposed model had 20% difference intervals.
Keywords: hypertriglyceridemie; Monitoring, Physiologic; Calculation; Extracellular Fluid; Level; Models, Biological; krysa rodu Rattus; zvířata; Blood Glucose; Hypertriglyceridemia; monitorování fyziologických funkcí; biologický transport; Male; krevní glukóza; Glucose; biologické modely; extracelulární tekutina; Blood; Rats; Interstitial; Animals; mužské pohlaví; Disease Models, Animal; Biological Transport; modely nemocí na zvířatech